Effective Expansion: Balance between Shrinkage and Hygroscopic Expansion. (May 2016) - Suiter, E.A.; Watson, L.E.; Tantbirojn, D.; Lou, J.S.B.; Versluis, A.
The purpose of this study was to investigate the relationship between hygroscopic expansion and polymerization shrinkage for compensation of polymerization shrinkage stresses in a restored tooth. One resin-modified glass-ionomer (RMGI) (Ketac Nano, 3M ESPE), 2 compomers (Dyract, Dentsply; Compoglass, Ivoclar), and a universal resin-based composite (EsthetX HD, Dentsply) were tested. Volumetric change after polymerization ("total shrinkage") and during 4 wk of water storage at 37°C was measured using an optical method ( n = 10). Post-gel shrinkage was measured during polymerization using a strain gauge method ( n = 10). Extracted human molars with large mesio-occluso-distal slot preparations were restored with the tested restorative materials. Tooth surfaces at baseline (preparation), after restoration, and during 4 wk of 37°C water storage were scanned with an optical scanner to determine cuspal flexure ( n = 8). Occlusal interface integrity was measured using dye penetration. Data were analyzed using analysis of variance and post hoc tests (significance level 0.05). All tested materials shrunk after polymerization. RMGI had the highest total shrinkage (4.65%) but lowest post-gel shrinkage (0.35%). Shrinkage values dropped significantly during storage in water but had not completely compensated polymerization shrinkage after 4 wk. All restored teeth initially exhibited inward (negative) cuspal flexure due to polymerization shrinkage. Cuspal flexure with the RMGI restoration was significantly less (–6.4 µm) than with the other materials (−12.1 to −14.1 µm). After 1 d, cuspal flexure reversed to +5.0 µm cuspal expansion with the RMGI and increased to +9.3 µm at 4 wk. After 4 wk, hygroscopic expansion compensated cuspal flexure in a compomer (Compoglass) and reduced flexure with Dyract and resin-based composite. Marginal integrity (93.7% intact restoration wall) was best for the Compoglass restorations and lowest (73.1%) for the RMGI restorations. Hygroscopic expansion was more effective in compensating shrinkage stress than would be assumed based on total shrinkage, because only post-gel shrinkage needed compensation. Effective expansion is therefore hygroscopic expansion minus post-gel shrinkage.